"What about the child issue?" Group negotiations of gender and parenthood contracts in recruitment situations. (28th July 2017) - Löfstrand, Pär; Zakrisson, Ingrid
ABSTRACT: Men and women becoming parents are supposed to have equal opportunities in working life. However, inequality and discrimination are not easily avoided. The aim of this study was to investigate how argumentation related to parenthood and careers takes form in group discussions of a fictional recruitment situation, and how stereotypes such as competence and warmth are manifested in such discussions. Thirty-five ad-hoc groups of university students were asked to make a choice between three candidates for a consultancy position. The first two candidates were a man and a woman, while the third alternately was described either as a man or a woman described as having a newborn child. Parenthood was sometimes seen as reducing competence, but it was more often viewed as adding to competence. Parenthood was also considered to add warmth to the organization. Interestingly, all groups avoided relating the parenthood issue to gender. Three conversation patterns were found, differing in the amount of elaboration of the topic of parenthood and work. It was concluded that the most elaborated kind seems to foster a situation where implicit norms are made visible more easily.